Responsible Factors of Panic Buying: An Observation From Online Media Reports - Arafat, S. M. Yasir; Kar, Sujita Kumar; Menon, Vikas; Alradie-Mohamed, Angi; Mukherjee, Srijeeta; Kaliamoorthy, Charanya; Kabir, Russell (Frontiers in Public Health, 2020)
Background: Panic buying is an erratic human behavior that has been reported irregularly and episodically. There is a dearth of studies exploring the identifiable factors accounting for it. We aimed to identify the factors responsible for panic buying extracted from online media reports. Methods: We scrutinized the media reports published in English discussing the different aspects of panic buying. We collected data until May 30, 2020, and searched the possible mentioned reasons responsible for panic buying. Results: We analyzed a total of 784 media reports. The majority of the reports were found in Bing (18%), Ecosia (12.6%), Google (26.4%), and Yahoo (12.5%). Panic buying was reported in 93 countries. Among the 784 responses, a total of 171 reports did not explain the responsible factors of panic buying. Therefore, we analyzed the remaining 613 reports to identify the same. A sense of scarcity was reportedly found as the important factor in about 75% of the reports followed by increased demand (66.07%), the importance of the product (45.02%), anticipation of price hike (23.33%), and due to COVID-19 and its related factors (13.21%). Other reported factors were a rumor, psychological factors (safety-seeking behavior, uncertainty, anxiety reduction, and taking control), social learning, lack of trust, government action, and past experience. Conclusions: The study revealed the responsible factors of panic buying extracted from media reports. Further, studies involving the individuals indulging in panic buying behavior are warranted to replicate the findings.